Factors affecting the reactivity of thiol-functionalized mesoporous silica adsorbents toward mercury(II) - Delacôte, Cyril; Gaslain, Fabrice O.M.; Lebeau, Bénédicte; Walcarius, Alain (Talanta (Oxford), 2009)
Numerous mercaptopropyl-functionalized silica spheres have been prepared by either post-synthesis grafting of MCM-41 and MCM-48 or self-assembly co-condensation of mercaptopropyltrimethoxysilane (MPTMS) or mercaptopropyltriethoxysilane (MPTES) and tetraethoxysilane (TEOS) precursors in hydroalcoholic medium in the presence of a cationic surfactant as templating agent and ammonia as catalyst. These materials of approximately the same particle size and morphology featured different functionalization levels, various degrees of structural order, and variable distribution of thiol groups in the mesopores. Their reactivity in solution has been studied using Hg(II) as model analyte. Total accessibility (on a 1:1 S:Hg stoichiometry basis) was demonstrated and quantified for well-ordered materials whereas less open and less organized structures with high degrees of functionalization were subject to less-than-complete loadings. Capacities measured at pH 2 were lower than at pH 4 because of distinct mercury-binding mechanisms. Kinetics associated to the uptake process were studied by in situ electrochemical monitoring of Hg(II) consumption from aqueous suspensions containing the various adsorbents. They indicate only little difference between materials of the MCM-41 and MCM-48 series at similar functionalization levels, fast mass transport in well-ordered mesostructures in comparison to the poorly or non-ordered ones (except at pH 2 where charge formation induced some restriction in materials characterized by long-range structural order), and even faster processes in the wormlike frameworks (characterized by shorter range structural order). Hg(II) binding to thiol-functionalized materials obtained by post-synthesis grafting was found to occur more rapidly in the early beginning of the uptake process as a result of a higher concentration of binding sites at the pore entrance in comparison to the more homogeneous distribution of these groups in the mesochannels of materials obtained by co-condensation.